VOLITIONAL SPHERE DEVELOPMENT OF STUDENTS-PROSPECTIVE PRESCHOOL TEACHERS - Nesyna, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This article focuses on the problem of volitional sphere developing as an important part of human individuality. The theoretical basis is O. Grebenyuk’s individuality concept. In it, the individuality is defined as the unity of seven spheres, including volitional one which characterise the originality and uniqueness of a person. Positive development of volitional sphere affects self-development and success of preschool teacher's professional activity. This study adresses three key issues. First, it looks at the problem of volitional sphere in preschool teacher’s individuality and identifies the system of professionally important components. Second, it turns to examine dynamics of students ' volitional sphere during professional training at the university. Finally, the paper considers professionally important components of the volitional sphere that need to be developed. The data for this study were collected using the questionnaire “The Technique of Student’s Individuality” by T. Grebenyuk. Sixty-three students were recruited for this research. The participants study at Immanuel Kant Baltic Federal University, they are future preschool teachers. The results suggest that the structure of the volitional sphere changes from the first to the fourth year of study. In the fourth year, the components, that influence the development of subjectivity, dominate. The capacity for prolong volitional effort is not sufficiently developed among all participants in the study.